2008
DOI: 10.1080/07418820801954613
|View full text |Cite
|
Sign up to set email alerts
|

The Strategic Prevention of Gun Violence Among Gang‐Involved Offenders

Abstract: Problem-oriented policing has been suggested as a promising way to understand and prevent complex gang violence problems. A number of jurisdictions have been experimenting with new problem-oriented frameworks to understand and respond to gun violence among gang-involved offenders. These interventions are based on the "pulling levers" deterrence strategy that focuses criminal justice and social service attention on a small number of chronically offending gang members responsible for the bulk of urban gun violen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 43 publications
2
64
0
3
Order By: Relevance
“…3 In Los Angeles the evaluation showed that focused enforcement produced a significant short-term reduction in violent and gang crime in target areas relative to comparison areas (Tita et al 2003). Braga et al (2008) conducted analyses of before-and-after trends in gun violence and found a reduction in Lowell that was consistent with a unique program effect relative to other major Massachusetts cities. An evaluation of the Stockton initiative shows a statistically significant reduction in gun homicide following implementation of their pulling levers program while simultaneously showing that eight additional mid-sized cities in California (i.e., comparison sites similar to Stockton) did not experience a decline during the same period (Braga 2008).…”
Section: Assessing the Pulling Levers Interventionmentioning
confidence: 84%
“…3 In Los Angeles the evaluation showed that focused enforcement produced a significant short-term reduction in violent and gang crime in target areas relative to comparison areas (Tita et al 2003). Braga et al (2008) conducted analyses of before-and-after trends in gun violence and found a reduction in Lowell that was consistent with a unique program effect relative to other major Massachusetts cities. An evaluation of the Stockton initiative shows a statistically significant reduction in gun homicide following implementation of their pulling levers program while simultaneously showing that eight additional mid-sized cities in California (i.e., comparison sites similar to Stockton) did not experience a decline during the same period (Braga 2008).…”
Section: Assessing the Pulling Levers Interventionmentioning
confidence: 84%
“…A further realm of effectiveness emerged in the Group slab, although we know much less about these interventions than about interventions targeting individuals. The research that does exist seems to indicate that highly proactive and specific tactics such as the "pulling levers" approach (see Braga et al 2008;Kennedy 2009) are promising.…”
Section: Visual Patternsmentioning
confidence: 96%
“…These might involve, as Weisburd and Eck (2004) describe, the coordination of multiple agencies that handle different aspects of a particular problem, and they target specific mechanisms that produce crime. Specific programs might include using nuisance abatement laws to reduce drug dealing on a street block (e.g., Mazerolle et al 2000); using specific prosecution schemes against those who are caught selling drugs and armed with a weapon (e.g., Abrahamse et al 1991); employing the "pulling levers" approach against gang activity, which involves a combination of specific deterrencerelated interventions (see Braga et al 2001Braga et al , 2008McGarrell et al 2006); or targeting specific risk factors for juvenile crime (e.g. Weisburd et al 2008a).…”
Section: Level Of Focusmentioning
confidence: 99%
“…Lowell's Project Safe Neighborhoods program was implemented in 2002 (Braga, Pierce, McDevitt, Bond, & Cronin, 2008). An interagency partnership comprised of justice organizations, community-based groups, and social service organizations was created based on gun violence data to focus law enforcement resources on violent gang members who were driving the firearms violence problem in Lowell, Massachusetts.…”
Section: Program (Citation) Location Intervention Components Targetmentioning
confidence: 99%
“…To evaluate the Lowell PSN, Braga et al (2008) conducted a time series analysis on monthly counts of monthly gun violence incidents from 1996-2005, including homicide and aggravated assault. Braga et al (2008) report a 43% reduction in monthly assaultive gun violence incidents.…”
Section: Program (Citation) Location Intervention Components Targetmentioning
confidence: 99%